Hubungan Tingkat Pengetahuan dan Sikap dengan Perilaku Remaja Putri tentang Kebersihan Organ Reproduksi saat Menstruasi di SMP Pertiwi 1 Kota Jambi - Hesty Hesty; Maimaznah Maimaznah; Muhammad Hidayat (Universitas Baiturrahim, 2026)
Adolescent girls who have experienced menstruation need to have a good understanding of reproductive health. Improper menstrual hygiene practices can increase the risk of reproductive tract infections (RTIs), which in the long term can impact fertility. Data shows that reproductive tract infections remain a health problem for adolescent girls, mainly due to a lack of knowledge and inappropriate personal hygiene practices. A preliminary study at SMP Pertiwi 1, Jambi City, showed that 3 out of 6 female students experienced genital itching accompanied by an unpleasant odor, and there were still inappropriate behaviors in maintaining hygiene during menstruation. This condition indicates the potential for reproductive health problems in the school environment. This study aims to determine the relationship between knowledge and attitudes with reproductive organ hygiene behavior during menstruation in adolescent girls at SMP Pertiwi 1, Jambi City. This study used an observational analytical design with a cross-sectional approach. The population in this study were all 36 eighth-grade female students of SMP Pertiwi 1, Jambi City. A sample of 36 respondents was taken using a total sampling technique. The independent variables in this study were knowledge and attitudes, while the dependent variable was reproductive organ hygiene behavior during menstruation. Data were collected using a structured questionnaire based on the theory of adolescent reproductive health and menstrual personal hygiene, then analyzed univariately and bivariately using the Chi-Square test. The study was conducted from September 2024 to August 2025. The results of the bivariate test showed no significant relationship between knowledge and behavior (p = 0.292) or between attitudes and behavior (p = 1.000). The conclusion of this study is that there is no significant relationship between the level of knowledge and attitudes with reproductive organ hygiene behavior during menstruation in adolescent girls at SMP Pertiwi 1, Jambi City. It is recommended that schools integrate reproductive health education into the curriculum or UKS activities to improve understanding and practice of menstrual hygiene more optimally